Effect of Decorin and Bevacizumab on oxygen-induced retinopathy in rat models: A comparative study - Guler, Seda Duran; Balbaba, Mehmet; Colakoglu, Neriman; Bulmus, Ozgor; Ulas, Fatih; Eroksuz, Yesari (Wolters Kluwer Medknow Publications, 2021)
Purpose: The aims of this study were to evaluate the effects of decorin (DCN) in rat oxygen-induced retinopathy (OIR) model and to compare the results with those of bevacizumab. Methods: Twenty-eight newborn Sprague-Dawley rats were randomly divided into four groups. Group I (control): normoxia plus intraperitoneal (ip) normal saline (NS), Group II (sham): OIR plus ip NS, Group III (DCN): OIR plus ip 0.1 mg/kg DCN, and Group IV (bevacizumab): OIR plus ip 2.5 mg/kg bevacizumab. The OIR model was induced by cycling the oxygen concentration between 50% and 10% every 24 h for 14 days following their birth. In all groups, injections were administered on postnatal day (PD) 15. All animals were sacrificed and their right eyes were enucleated on PD 18. The nuclei of neovascular endothelial cells on the vitreal side of the inner limiting membrane were counted, and vascular endothelial growth factor (VEGF) and tumor necrosis factor-alpha (TNF)-alpha immunoreactivity were detected in histopathological and immunohistochemical examinations. One-way analysis of variance and post hoc Tukey tests were used for statistical analyses of the data. Results: In Groups II, III, and IV, the mean neovascular cell nuclei counts were 13.14 +/- 1.34, 6.57 +/- 1.51, and 6.71 +/- 1.49, respectively. The mean neovascular cell nuclei count was significantly reduced in treatment groups compared with sham group (P < 0.001). In immunohistochemical staining, the immunoreactivity of VEGF was 0.07 +/- 0.02, 0.97 +/- 0.21, 0.37 +/- 0.12, and 0.23 +/- 0.17, respectively. Likewise, immunoreactivity of TNF-alpha was 0.02 +/- 0.02, 1.11 +/- 0.36, 0.37 +/- 0.13, and 0.62 +/- 0.21, respectively. VEGF and TNF-alpha immunoreactivity increased markedly in the sham group compared with those in the control group (P < 0.001). VEGF and TNF-alpha immunoreactivity of treatment groups decreased significantly compared to sham group (P < 0.001). Conclusion: The beneficial effects obtained by DCN administration in OIR model were comparable to the effects of bevacizumab.
Keywords: Bevacizumab; decorin; oxygen-induced retinopathy; retinopathy of prematurity; vascular endothelial growth factor